2017
DOI: 10.3892/mmr.2017.6627
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide inhibits mitochondrial fission in neuroblastoma N2a cells through the Drp1/ERK1/2 signaling pathway

Abstract: Hydrogen sulfide (H2S) has been demonstrated to have various effects on mitochondrial function. The aim of the present study was to investigate the effects of H2S on mitochondrial fission and the potential underlying mechanisms of these effects. Transmission electron microscopy analysis demonstrated that sodium hydrosulfide (NaHS, a donor of H2S) inhibited mitochondrial fission in a dose‑ and time‑dependent manner. Treating neuro‑2a (N2a) mouse neuroblastoma cells with 400 µM NaHS for 16 h significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…As shown in Figures 2A,B, we observed elongated and tubular mitochondria in HEI-OC1 cells, then they became highly fragmented upon the loss of Opa1. In Neuro 2a cells, in contrast, fragmented mitochondria were observed by MitoTracker staining even in untreated control cells (data not shown), which is consistent with a previous report that only 30% of mitochondria in this cell line had a length at least twice their width when observed by transmission electron microscopy (Qiao et al, 2017). Because of this, we were unable to observe a change in mitochondrial shape following Opa1 knockdown in Neuro 2a cells, as assessed by MitoTracker staining.…”
Section: Discussionsupporting
confidence: 92%
“…As shown in Figures 2A,B, we observed elongated and tubular mitochondria in HEI-OC1 cells, then they became highly fragmented upon the loss of Opa1. In Neuro 2a cells, in contrast, fragmented mitochondria were observed by MitoTracker staining even in untreated control cells (data not shown), which is consistent with a previous report that only 30% of mitochondria in this cell line had a length at least twice their width when observed by transmission electron microscopy (Qiao et al, 2017). Because of this, we were unable to observe a change in mitochondrial shape following Opa1 knockdown in Neuro 2a cells, as assessed by MitoTracker staining.…”
Section: Discussionsupporting
confidence: 92%
“…While changes in mitochondrial fission are likely mediated by the coordinated interplay among complex signaling cascades modulating transcription, protein stability, and translocation of Drp1, a majority of Drp1 studies have focused on posttranslational modifications (e.g., phosphorylation, S-nitrosylation, and SUMOylation) that affect protein stability and the interaction with factors that facilitate translocation. However, relatively few studies to date have addressed the regulatory pathways that modulate the transcription of Dnm1l in physiological and pathophysiologic states (36,37). Here, we showed that Dnmt1-dependent DNA methylation is crucial for sustaining physiological level of Dnm1l expression in adipocytes.…”
Section: Discussionmentioning
confidence: 77%
“…At present there are few data on the influence of H 2 S the total number of MC in cells. However, it is believed that H 2 S exerts different effects on the number, function, and dynamics of MC depending on the used dose [29]. Probably the presumed concentration is effective for increasing the number of organelles.…”
Section: Discussionmentioning
confidence: 99%